Mastering English Diphthongs: Phonological Challenges and Patterns Among Sikka Students in Yogyakarta - Soge, Edeltrudis Patrisia; Hindom, Simron Krinuartjati; Ena, Ouda Teda (Universitas Muhammadiyah Mataram, 2025)
This study explores the pronunciation of English diphthongs by Sikka students in Yogyakarta, focusing on the phonological challenges and patterns that emerge. The researcher used descriptive qualitative by employing interviews and observations. The participants were ten Sikka students aged 19-34 with varying English learning backgrounds. The researcher asked students to read a text that had diphthongs and compared students' English diphthong pronunciation with the Oxford Dictionary (1995) and Longman Dictionary (2008). The findings show that despite the duration of English language exposure, the participants had difficulties pronouncing English diphthongs correctly. The text contained eight diphthongs, which were included in nineteen words. The data demonstrate that most participants incorrectly pronounced eleven words, which were included in six diphthongs, whilst simultaneously pronouncing eight words, which were included in eight diphthongs, correctly. Analysis indicates that the mispronunciations stem from factors such as the absence of similar diphthongs in the Sikka language, unfamiliarity with English phonology, limited practice, and a lack of focus on diphthongs during language learning. The research addresses a gap in current literature by exploring the impact of the Sikka language, a prevalent local language, on English pronunciation.